Cork and Alcoholic Beverages (Food Reviews International, 2005)
For centuries, cork has been the stopper of choice for various alcoholic beverages. In this review, cork history, sources, production, physical properties, composition, off-flavors, and alternatives to cork stoppers are discussed.
doi: 10.1081/FRI-200040593